Dilema Audit Kinerja: Antara Pengawasan Seremonial dan Perbaikan Nyata - M. Irsan Nasution; Mutia Riska Faridani (MAN 4 Kota Pekanbaru, 2025)
This study investigates the dilemma of performance auditing in Indonesia’s public sector through a systematic review of 30 articles published from 2015–2024 using the PRISMA 2020 protocol. Findings show that audits remain largely ceremonial, indicated by a low recommendation implementation rate averaging 12% and the use of audit results for political legitimacy rather than substantive improvement. Analyses of the New Capital City (IKN) project and COVID-19 social assistance reveal that major findings by the Audit Board of Indonesia (BPK) in 2022–2023 were followed mostly by administrative corrections instead of structural reforms. Key barriers include political costs, limited auditor capacity, and weak follow-up monitoring. Evidence from Central Java shows that participatory audits can raise implementation rates by up to 40% through greater horizontal accountability. This study introduces the concept of “political ceremonialism” and recommends stronger monitoring units, integrated e-audit systems, outcome-based competencies, and improved sanctions.